E-Marketing Applications Based On Virtual Reality Using Sostac Planning Method On Sales Property - Philip Kristy Wijaya; Aditiya Hermawan (Tech-E, 2018)
Increased demand for property in Indonesian society, opening up a great opportunity for entrepreneurs to start a business in the property sector. The large number of new entrepreneurs, opening up many different ways of offering attractive products and promos that bring the impact of significant sales decline for those who can not compete. One such problem-solving proposal is to analyze current conditions and create new, powerful goals and strategies to implement. The methods that can serve as guidelines in the analysis and planning of the marketing strategy are SOSTAC (Situation Analysis, Objectives Setting, Strategy, Tactics, Action and Control). Based on the results of SOSTAC analysis and suggestions the way that can be done is to build E-Marketing with media websites that can be easily reached by the public and a marketing tool for marketing executive. On the website created a Virtual Reality feature that can display the form of building to consumers to increase consumer confidence in purchasing units. Based on testing and evaluation by consumers a new marketing strategy plan is worth trying and applied in marketing strategy.